2001
DOI: 10.1590/s0034-89102001000600006
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: Resumen ObjetivoEl estrato socioeconómico juega un rol importante en las desigualdades en salud. En México, la prevalencia más alta de casos de SIDA se encuentra en población de estratos más bajos. El propósito de lo estudio fue describir el estrato socioeconómico (ajustado por variables psicosociales, situacionales y demográficas) como un factor predictor del uso consistente del condón, en adolescentes. Métodos Se incluyó en el estudio una muestra de una encuesta previa aplicada a 1.410 adolescentes de 15 a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…In regards to self-reported condom use behaviors, while the majority of adolescents reported inconsistent condom use, consistent condom use among this sample is higher compared to that of other studies conducted on Mexican adolescents (Caballero Hoyos & Villasenor Sierra, 2001; Villasenor-Sierra et al, 2002). In addition, unlike other studies, our sample reported higher use of condoms at first intercourse (Antrop et al, 2006; Gayet, Juarez, Pedrosa, & Magis, 2003; Tapia-Aguirre et al, 2004; Walker, Torres, Gutierrez, Flemming, & Bertozzi, 2004).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In regards to self-reported condom use behaviors, while the majority of adolescents reported inconsistent condom use, consistent condom use among this sample is higher compared to that of other studies conducted on Mexican adolescents (Caballero Hoyos & Villasenor Sierra, 2001; Villasenor-Sierra et al, 2002). In addition, unlike other studies, our sample reported higher use of condoms at first intercourse (Antrop et al, 2006; Gayet, Juarez, Pedrosa, & Magis, 2003; Tapia-Aguirre et al, 2004; Walker, Torres, Gutierrez, Flemming, & Bertozzi, 2004).…”
Section: Discussioncontrasting
confidence: 77%
“…Findings from condom use studies (e.g., Antrop, Walker, Gutierrez, & Bertozzi, 2006; Caballero Hoyos & Villasenor Sierra, 2001; Givaudan, Van de Vijver, Poortinga, Leenen, & Pick, 2007; Martinez-Donate et al, 2004) consistently demonstrate that condom use among Mexican adolescents is inconsistent. In a sample of high school students 15 to 19 years old, less than one-third of the sample reported always using condoms (Caballero Hoyos & Villasenor Sierra, 2001).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Critics of this approach cite the "ABC" policy (Abstinance, Behaviour, Condoms) (Coates et al, 2008) as being sufficient. While condoms are 80-90% effective if always used properly (Halperin et al, 2004), including during foreplay, the reality is that for a host of reasons such as passion over-riding common sense, dislike for condoms, reckless behaviour often fuelled by inebriation, and/or not having a condom available, many people either do not use them consistently or at all (Donovan & Ross, 2000;Szabo & Short, 2000;Caballero-Hoyos & Villasenor-Sierra, 2001;Ferrante et al, 2005;Jadack et al, 2006;Kang et al, 2006;Sanchez et al, 2006;Yahya-Malima et al, 2007;Munro et al, 2008;Wawer et al, 2009). This research included RCTs in which men were given counselling and free condoms .…”
Section: Male Circumcision For Hiv Preventionmentioning
confidence: 99%
“…The girls had a smaller number of sexual partners when compared to boys. And although this pattern is explained due to the gender difference, some authors do not coverthis difference [21][22][23] . Similar results to ours were reported by Silva et al 24 , who in addition to verifying that same standard, they still infer that the chances of being exposed to sexually transmitted diseases (STDS) and to human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is greater in adolescents who have a higher number of sexual partners, with the increased risk to each new partner.…”
mentioning
confidence: 97%